2013
DOI: 10.3892/mmr.2013.1520
|View full text |Cite
|
Sign up to set email alerts
|

Arazyme inhibits cytokine expression and upregulates skin barrier protein expression

Abstract: Abstract. In the present study, the inhibitory effect of arazyme on allergic inflammation was investigated by evaluating the alteration of cytokine production and expression of skin barrier proteins in immune and HaCaT human keratinocyte cells. THP-1 human monocytic and EoL-1 human eosinophilic cells were treated with Dermatophagoides pteronissinus extract (DpE). Monocyte chemotactic protein-1 (MCP-1)/CCL2, interleukin (IL)-6 and IL-8 increased following DpE treatment and arazyme significantly blocked the incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Recently, Kim and collaborators [57] showed that arazyme inhibited the secretion of inflammatory mediators by human immortalized keratinocytes (HaCaT) and monocytic (THP-1) or eosinophilic (EoL-1) tumor cell lines in vitro . These cells were stimulated, and treatment with arazyme reduced the expression of IL-6, IL-8, MCP-1/CCL-2 and TARC/CCL-17, suggesting that arazyme may also have an immunomodulatory effect in vivo , that should be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kim and collaborators [57] showed that arazyme inhibited the secretion of inflammatory mediators by human immortalized keratinocytes (HaCaT) and monocytic (THP-1) or eosinophilic (EoL-1) tumor cell lines in vitro . These cells were stimulated, and treatment with arazyme reduced the expression of IL-6, IL-8, MCP-1/CCL-2 and TARC/CCL-17, suggesting that arazyme may also have an immunomodulatory effect in vivo , that should be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous proteases are involved in several biological processes related to cancer, infectious diseases, and inflammation [15]. Previous studies have reported the effects of arazyme, including anti-atopic, anti-inflammatory, and hepatoprotective effects [16,17,18,19]. However, the hepatoprotective effects of arazyme in chronic NAFLD have not been documented.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, arazyme may aggravate the pathogenesis of allergic diseases. However, we elucidated anti-inflammatory effect of arazyme in keratinocytes and endothelial cells (Kim et al, 2013;Kim et al, 2014b). Arazyme has also been shown to effectively alleviate clinical features of atopic dermatitis in an atopic dermatitis-like mouse model.…”
Section: Discussionmentioning
confidence: 97%
“…Arazyme is a metalloprotease that induces anti-inflammatory responses such as downregulation of cytokine and reactive oxygen species (ROS) production (Kim et al, 2013;Kim et al, 2014b). We recently found arazyme to be a useful drug candidate for treatment of atopic dermatitis (Kim et al, 2014a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation